Antibacterial ceramics and preparation methods thereof
By using specific raw materials combinations in the blank and antibacterial coating of antibacterial ceramics, the problem of poor bacterial control effect during high-temperature firing is solved, and long-lasting antibacterial and antibacterial properties are achieved, and it is not harmful to human cells.
Patent Information
- Application Number
- CN202410754898.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-06-12
AI Technical Summary
Existing antibacterial ceramics have poor bacteria control effects during high temperature firing. Silver products may be harmful to human cells. Titanium products require photocatalysis and the bacterial control membrane is prone to fall off.
The blank consisting of lene, cordierite, montmorillonite, etc. is used, and the surface coating is added graphene oxide, modified red mud and other components to the surface coating. Through the synergy between the blank and the antibacterial coating, lasting antibacterial properties are achieved.
The antibacterial ceramic has excellent antibacterial properties and antibacterial properties after high temperature firing. It does not rely on photocatalysis, and is not easy to lead to bacterial adhesion and has stable performance.
Smart Images

Figure BDA0004889153760000071 
Figure BDA0004889153760000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial ceramics, and specifically relates to an antibacterial ceramic and a preparation method thereof. Background Art
[0002] Antibacterial ceramics are a new type of functional material that protects the environment with high technical content. While maintaining the original use functions and decorative effects of ceramic products, they add antibacterial and chemical degradation functions, so they can be widely used in health, medical, family homes, civil or industrial buildings, and have broad application prospects.
[0003] Antibacterial ceramics are the product of the combination of antibacterial technology and ceramic materials, and also the product of the combination of materials science and microbiology. Throughout the development history of antibacterial ceramics, the manifestation of its antibacterial properties mainly relies on inorganic antibacterial materials such as metallic silver, rare earth and photocatalytic types. Due to various reasons, the effect of organic antibacterial agents in antibacterial ceramics is far inferior to that of inorganic antibacterial materials.
[0004] Among antibacterial ceramics, silver-based antibacterial ceramics and titanium-based antibacterial ceramics are the most common. Silver-based antibacterial effects are very good, but the disadvantages are: if silver ions are applied to ceramics during high-temperature firing, the glaze will change color, making the glaze unsightly. If the amount of silver ions is insufficient, the bactericidal effect is not ideal. In addition, silver ions will evaporate during high-temperature firing, resulting in poor bacteria control effects. The most important thing is that modern scientific research has found that silver ions and gold ions can kill bacteria and human cells. This discovery makes people worry about whether long-term use of silver-based bacteria control products is harmful to the body. The disadvantages of titanium-based antibacterial ceramics are: poor bacteria control effects during high-temperature firing, and photocatalysis is required for sterilization; the bacteria control film and ceramics are easy to fall off.
[0005] In view of the above technical shortcomings, it is necessary to explore a new type of antibacterial ceramics. Summary of the invention
[0006] The purpose of the present invention is to provide an antibacterial ceramic which can reduce bacterial adhesion and has excellent antibacterial properties; the present invention also provides a preparation method thereof.
[0007] The antibacterial ceramic of the present invention is composed of a body and an antibacterial coating; the body is composed of the following raw materials in parts by weight: 40-43 parts of pyrophyllite, 12-15 parts of cordierite, 17-19 parts of montmorillonite, 10-12 parts of wollastonite, 7-9 parts of magnesite, 6-8 parts of barite, 5-7 parts of cryolite, 4-6 parts of lithium porcelain stone, 7-9 parts of silicon nitride, 11-13 parts of boron mud, 1-3 parts of nano lanthanum oxide, and 5-7 parts of nano zinc phosphate; the antibacterial coating is composed of the following raw materials in parts by weight: 2-3 parts of graphene oxide, 7-9 parts of modified red mud, 0.5-1.5 parts of 2-bromo-2-nitropropane-1,3-diol, 1.2-1.6 parts of polyvinylidene fluoride, 17-19 parts of N-methylpyrrolidone, and 1-2 parts of perfluorodecyltriethoxysilane.
[0008] Preferably, the green body is composed of the following raw materials, by weight: 42 parts of pyrophyllite, 14 parts of cordierite, 18 parts of montmorillonite, 11 parts of wollastonite, 8 parts of magnesite, 7 parts of barite, 6 parts of cryolite, 5 parts of lithium porcelain stone, 8 parts of silicon nitride, 12 parts of boron mud, 2 parts of nano-lanthanum oxide, and 6 parts of nano-zinc phosphate.
[0009] Preferably, the antibacterial coating is composed of the following raw materials in parts by weight: 2.5 parts of graphene oxide, 8 parts of modified red mud, 1.0 parts of 2-bromo-2-nitropropane-1,3-diol, 1.4 parts of polyvinylidene fluoride, 18 parts of N-methylpyrrolidone, and 1.5 parts of perfluorodecyltriethoxysilane.
[0010] in:
[0011] The preparation method of modified red mud consists of the following steps:
[0012] (1) red mud was mixed with water, and hydrochloric acid was added to adjust the pH value of the system to 3, and then sodium hydroxide solution was added thereto to adjust the pH value of the system to 9, and finally the mixture was filtered and washed with water until neutral, and dried at 125° C. for 4 h to prepare pretreated red mud;
[0013] (2) The pretreated red mud was mixed with copper nitrate solution, reacted at 80° C. for 2.5 h, and then filtered and dried to prepare modified red mud.
[0014] in:
[0015] The mass ratio of red mud to water in step (1) is 1:1.5.
[0016] The mass volume ratio of the pretreated red mud to the copper nitrate solution in step (2) is 1:9, expressed in g / mL.
[0017] The concentration of the copper nitrate solution in step (2) is 0.17 mol / L.
[0018] The antibacterial ceramics described in the present invention have raw materials that interact with each other in the green body layer, and the compactness of the green body is improved after firing. In addition, a mixture of silicon nitride, boron mud, nano-lanthanum oxide and nano-zinc phosphate is creatively added to the green body layer, and the four interact with each other and are evenly dispersed in the green body, so that the green body has lasting antibacterial properties and is independent of photocatalytic sterilization. Among them, the silicon nitride surface is a micro-rough surface composed of protruding rod-shaped β-silicon nitride grains, which have a hexagonal cross-section and are intertwined to form a unique micron / nanoscale morphology. This morphology effectively reduces bacterial colonization, and silicon nitride is hydrophilic. This hydrophilic silicon nitride surface hinders the formation of bacterial biofilms through protein adsorption and cell viscosity, thereby playing an antibacterial role. In addition, silicon nitride can also inhibit the adhesion and proliferation of Gram-positive bacteria and Gram-negative bacteria. During the firing process, boron mud produces active magnesium oxide, which has strong antibacterial properties against Gram-positive bacteria, and the boron element has long-lasting antibacterial and bactericidal effects; nano-lanthanum oxide hinders the synthesis of peptidoglycan, the main component of the bacterial cell wall, combines with the hydrophobic hydroxyl groups in the protein inside the bacterial cell, destroys the bacterial sheath and wall structure, causes the bacteria to lose their original functions and gradually die; nano-zinc phosphate has a broad-spectrum antibacterial property and can inhibit the growth of most bacteria and fungi. Nano-zinc phosphate mainly achieves its antibacterial purpose by combining with the bacterial cell membrane and membrane protein, destroying its structure, and after entering the cell, destroying the enzymes of the electron transfer system and reacting with DNA.
[0019] The antibacterial ceramic of the present invention has an antibacterial coating on the surface of the green body, and the antibacterial coating is composed of graphene oxide, modified red mud, 2-bromo-2-nitropropane-1,3-diol, polyvinylidene fluoride, N-methylpyrrolidone and perfluorodecyltriethoxysilane. The graphene oxide, modified red mud and 2-bromo-2-nitropropane-1,3-diol have excellent antibacterial properties. After being modified with polyvinylidene fluoride and perfluorodecyltriethoxysilane, the antibacterial coating is given hydrophobicity, thereby reducing the attachment of bacteria, so that the antibacterial coating has antibacterial properties. Among them: graphene oxide physically wraps the trapped bacterial cells, cuts off the connection between the cells and the environment, thereby affecting cell metabolism, preventing cell reproduction, and achieving the effect of cell apoptosis; red mud is enriched with copper ions after modification, and copper ions interfere with the cell metabolism process of bacteria to make them lose their due biological functions, eventually leading to bacterial cell death and sterilization; 2-bromo-2-nitropropane-1,3-diol has broad-spectrum antibacterial activity and can effectively inhibit Gram-positive and negative bacteria, yeasts and molds. Therefore, graphene oxide, modified red mud and 2-bromo-2-nitropropane-1,3-diol interact with each other to ensure broad-spectrum antibacterial properties.
[0020] The method for preparing the antibacterial ceramic of the present invention comprises the following steps:
[0021] (1) mixing the green body raw materials uniformly according to the weight ratio, wet ball milling into slurry, dry grinding to obtain powder, and pressing the powder into a green body by molding;
[0022] (2) drying the green body and then firing it, cooling it to room temperature at a cooling rate of 5-7° C. / h to obtain an antibacterial ceramic green body;
[0023] (3) dissolving graphene oxide and polyvinylidene fluoride in N-methylpyrrolidone to prepare a first solution; then dissolving modified red mud and 2-bromo-2-nitropropane-1,3-diol in perfluorodecyltriethoxysilane to prepare a second solution; adding the first solution to the second solution and stirring to prepare an antibacterial coating solution;
[0024] (4) Spraying the antibacterial coating liquid onto the antibacterial ceramic body prepared in step (2), and then drying to obtain the antibacterial ceramic.
[0025] in:
[0026] The mass of water added during wet ball milling in step (1) accounts for 35% of the mass of the green body raw material and water, and the ball milling time is 18 hours.
[0027] In step (1), the drying temperature is 100-105° C. and the drying time is 7 hours.
[0028] The pressure of the powder pressing in step (1) is 60 MPa.
[0029] In step (2), the drying temperature is 105-110° C. and the drying time is 4 h.
[0030] The sintering in step (2) is to heat the temperature from room temperature to 750-800°C at a heating rate of 5°C / min and keep it at that temperature for 55-65min, and then heat the temperature to 1200-1225°C at a heating rate of 3°C / min and keep it at that temperature for 2.5-3h.
[0031] In step (3), the stirring temperature for preparing the first solution is room temperature, and the stirring time is 0.5 h; the stirring temperature for preparing the second solution is 130-135°C, and the stirring time is 0.8 h; the stirring temperature for the antibacterial coating liquid is room temperature, and the stirring time is 0.5 h.
[0032] In step (4), the drying temperature is 80-85° C. and the drying time is 4.5-5 h.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The antibacterial ceramic of the present invention has a synergistic effect between the green body and the antibacterial coating to ensure the durability and antibacterial properties of the ceramic. The raw materials in the green body layer interact with each other, and the compactness of the green body is improved by firing. The additionally added mixture of silicon nitride, boron mud, nano-lanthanum oxide and nano-zinc phosphate makes the green body have a durable antibacterial property. In addition, by providing a hydrophobic antibacterial coating on the green body, the prepared ceramic has the properties of reducing bacterial adhesion and antibacterial properties.
[0035] (2) The preparation method of the antibacterial ceramics described in the present invention has a simple process and is easy to realize industrial production. The performance of the prepared antibacterial ceramics is stable. DETAILED DESCRIPTION
[0036] The present invention is further described below with reference to the embodiments.
[0037] Example 1
[0038] The antibacterial ceramic described in Example 1 is composed of a body and an antibacterial coating; the body is composed of the following raw materials, by weight: 42 parts of pyrophyllite, 14 parts of cordierite, 18 parts of montmorillonite, 11 parts of wollastonite, 8 parts of magnesite, 7 parts of barite, 6 parts of cryolite, 5 parts of lithium porcelain stone, 8 parts of silicon nitride, 12 parts of boron mud, 2 parts of nano-lanthanum oxide, and 6 parts of nano-zinc phosphate; the antibacterial coating is composed of the following raw materials, by weight: 2.5 parts of graphene oxide, 8 parts of modified red mud, 1.0 part of 2-bromo-2-nitropropane-1,3-diol, 1.4 parts of polyvinylidene fluoride, 18 parts of N-methylpyrrolidone, and 1.5 parts of perfluorodecyltriethoxysilane.
[0039] in:
[0040] The preparation method of modified red mud consists of the following steps:
[0041] (1) red mud was mixed with water, and hydrochloric acid was added to adjust the pH value of the system to 3, and then sodium hydroxide solution was added thereto to adjust the pH value of the system to 9, and finally the mixture was filtered and washed with water until neutral, and dried at 125° C. for 4 h to prepare pretreated red mud;
[0042] (2) The pretreated red mud was mixed with copper nitrate solution, reacted at 80° C. for 2.5 h, and then filtered and dried to prepare modified red mud.
[0043] in:
[0044] The mass ratio of red mud to water in step (1) is 1:1.5.
[0045] The mass volume ratio of the pretreated red mud to the copper nitrate solution in step (2) is 1:9, expressed in g / mL.
[0046] The concentration of the copper nitrate solution in step (2) is 0.17 mol / L.
[0047] The method for preparing the antibacterial ceramic described in Example 1 comprises the following steps:
[0048] (1) mixing the green body raw materials uniformly according to the weight ratio, wet ball milling into slurry, dry grinding to obtain powder, and pressing the powder into a green body by molding;
[0049] (2) drying the green body and then firing it, cooling it to room temperature at a cooling rate of 6° C. / h to obtain an antibacterial ceramic green body;
[0050] (3) dissolving graphene oxide and polyvinylidene fluoride in N-methylpyrrolidone to prepare a first solution; then dissolving modified red mud and 2-bromo-2-nitropropane-1,3-diol in perfluorodecyltriethoxysilane to prepare a second solution; adding the first solution to the second solution and stirring to prepare an antibacterial coating solution;
[0051] (4) Spraying the antibacterial coating liquid onto the antibacterial ceramic body prepared in step (2), and then drying to obtain the antibacterial ceramic.
[0052] in:
[0053] The mass of water added during wet ball milling in step (1) accounts for 35% of the mass of the green body raw material and water, and the ball milling time is 18 hours.
[0054] In step (1), the drying temperature is 103° C. and the drying time is 7 h.
[0055] The pressure of the powder pressing in step (1) is 60 MPa.
[0056] In step (2), the drying temperature is 107° C. and the drying time is 4 h.
[0057] The sintering in step (2) is carried out by heating from room temperature to 780°C at a heating rate of 5°C / min and keeping the temperature for 60 minutes, and then heating to 1210°C at a heating rate of 3°C / min and keeping the temperature for 2.7 hours.
[0058] In step (3), the stirring temperature for preparing the first solution is room temperature, and the stirring time is 0.5 h; the stirring temperature for preparing the second solution is 133° C., and the stirring time is 0.8 h; the stirring temperature for the antibacterial coating liquid is room temperature, and the stirring time is 0.5 h.
[0059] In step (4), the drying temperature is 83° C. and the drying time is 4.7 h.
[0060] Example 2
[0061] The antibacterial ceramic described in Example 2 is composed of a body and an antibacterial coating; the body is composed of the following raw materials, by weight: 40 parts of pyrophyllite, 15 parts of cordierite, 17 parts of montmorillonite, 12 parts of wollastonite, 7 parts of magnesite, 8 parts of barite, 5 parts of cryolite, 6 parts of lithium porcelain stone, 7 parts of silicon nitride, 13 parts of boron mud, 3 parts of nano-lanthanum oxide, and 5 parts of nano-zinc phosphate; the antibacterial coating is composed of the following raw materials, by weight: 2 parts of graphene oxide, 9 parts of modified red mud, 0.5 parts of 2-bromo-2-nitropropane-1,3-diol, 1.6 parts of polyvinylidene fluoride, 17 parts of N-methylpyrrolidone, and 2 parts of perfluorodecyltriethoxysilane.
[0062] in:
[0063] The preparation method of modified red mud consists of the following steps:
[0064] (1) red mud was mixed with water, and hydrochloric acid was added to adjust the pH value of the system to 3, and then sodium hydroxide solution was added thereto to adjust the pH value of the system to 9, and finally the mixture was filtered and washed with water until neutral, and dried at 125° C. for 4 h to prepare pretreated red mud;
[0065] (2) The pretreated red mud was mixed with copper nitrate solution, reacted at 80° C. for 2.5 h, and then filtered and dried to prepare modified red mud.
[0066] in:
[0067] The mass ratio of red mud to water in step (1) is 1:1.5.
[0068] The mass volume ratio of the pretreated red mud to the copper nitrate solution in step (2) is 1:9, expressed in g / mL.
[0069] The concentration of the copper nitrate solution in step (2) is 0.17 mol / L.
[0070] The method for preparing the antibacterial ceramic described in this embodiment 2 comprises the following steps:
[0071] (1) mixing the green body raw materials uniformly according to the weight ratio, wet ball milling into slurry, dry grinding to obtain powder, and pressing the powder into a green body by molding;
[0072] (2) drying the green body and then firing it, cooling it to room temperature at a cooling rate of 5° C. / h to obtain an antibacterial ceramic green body;
[0073] (3) dissolving graphene oxide and polyvinylidene fluoride in N-methylpyrrolidone to prepare a first solution; then dissolving modified red mud and 2-bromo-2-nitropropane-1,3-diol in perfluorodecyltriethoxysilane to prepare a second solution; adding the first solution to the second solution and stirring to prepare an antibacterial coating solution;
[0074] (4) Spraying the antibacterial coating liquid onto the antibacterial ceramic body prepared in step (2), and then drying to obtain the antibacterial ceramic.
[0075] in:
[0076] The mass of water added during wet ball milling in step (1) accounts for 35% of the mass of the green body raw material and water, and the ball milling time is 18 hours.
[0077] In step (1), the drying temperature is 100° C. and the drying time is 7 h.
[0078] The pressure of the powder pressing in step (1) is 60 MPa.
[0079] In step (2), the drying temperature is 105° C. and the drying time is 4 h.
[0080] The sintering in step (2) is carried out by heating from room temperature to 750°C at a heating rate of 5°C / min and keeping the temperature for 65 minutes, and then heating to 1200°C at a heating rate of 3°C / min and keeping the temperature for 3 hours.
[0081] In step (3), the stirring temperature for preparing the first solution is room temperature, and the stirring time is 0.5 h; the stirring temperature for preparing the second solution is 130° C., and the stirring time is 0.8 h; the stirring temperature for the antibacterial coating liquid is room temperature, and the stirring time is 0.5 h.
[0082] In step (4), the drying temperature is 80° C. and the drying time is 5 h.
[0083] Example 3
[0084] The antibacterial ceramic described in Example 3 is composed of a body and an antibacterial coating; the body is composed of the following raw materials, by weight: 43 parts of pyrophyllite, 12 parts of cordierite, 19 parts of montmorillonite, 10 parts of wollastonite, 9 parts of magnesite, 6 parts of barite, 7 parts of cryolite, 4 parts of lithium porcelain stone, 9 parts of silicon nitride, 11 parts of boron mud, 1 part of nano-lanthanum oxide, and 7 parts of nano-zinc phosphate; the antibacterial coating is composed of the following raw materials, by weight: 3 parts of graphene oxide, 7 parts of modified red mud, 1.5 parts of 2-bromo-2-nitropropane-1,3-diol, 1.2 parts of polyvinylidene fluoride, 19 parts of N-methylpyrrolidone, and 1 part of perfluorodecyltriethoxysilane.
[0085] in:
[0086] The preparation method of modified red mud consists of the following steps:
[0087] (1) red mud was mixed with water, and hydrochloric acid was added to adjust the pH value of the system to 3, and then sodium hydroxide solution was added thereto to adjust the pH value of the system to 9, and finally the mixture was filtered and washed with water until neutral, and dried at 125° C. for 4 h to prepare pretreated red mud;
[0088] (2) The pretreated red mud was mixed with copper nitrate solution, reacted at 80° C. for 2.5 h, and then filtered and dried to prepare modified red mud.
[0089] in:
[0090] The mass ratio of red mud to water in step (1) is 1:1.5.
[0091] The mass volume ratio of the pretreated red mud to the copper nitrate solution in step (2) is 1:9, expressed in g / mL.
[0092] The concentration of the copper nitrate solution in step (2) is 0.17 mol / L.
[0093] The method for preparing the antibacterial ceramic described in this embodiment 3 comprises the following steps:
[0094] (1) mixing the green body raw materials uniformly according to the weight ratio, wet ball milling into slurry, dry grinding to obtain powder, and pressing the powder into a green body by molding;
[0095] (2) drying the green body and then firing it, cooling it to room temperature at a cooling rate of 7° C. / h to obtain an antibacterial ceramic green body;
[0096] (3) dissolving graphene oxide and polyvinylidene fluoride in N-methylpyrrolidone to prepare a first solution; then dissolving modified red mud and 2-bromo-2-nitropropane-1,3-diol in perfluorodecyltriethoxysilane to prepare a second solution; adding the first solution to the second solution and stirring to prepare an antibacterial coating solution;
[0097] (4) Spraying the antibacterial coating liquid onto the antibacterial ceramic body prepared in step (2), and then drying to obtain the antibacterial ceramic.
[0098] in:
[0099] The mass of water added during wet ball milling in step (1) accounts for 35% of the mass of the green body raw material and water, and the ball milling time is 18 hours.
[0100] In step (1), the drying temperature is 105° C. and the drying time is 7 h.
[0101] The pressure of the powder pressing in step (1) is 60 MPa.
[0102] In step (2), the drying temperature is 110° C. and the drying time is 4 h.
[0103] The sintering in step (2) is carried out by heating from room temperature to 800°C at a heating rate of 5°C / min and keeping the temperature for 55 minutes, and then heating to 1225°C at a heating rate of 3°C / min and keeping the temperature for 2.5 hours.
[0104] In step (3), the stirring temperature for preparing the first solution is room temperature, and the stirring time is 0.5 h; the stirring temperature for preparing the second solution is 135° C., and the stirring time is 0.8 h; the stirring temperature for the antibacterial coating liquid is room temperature, and the stirring time is 0.5 h.
[0105] In step (4), the drying temperature is 85° C. and the drying time is 4.5 h.
[0106] Comparative Example 1
[0107] The preparation method of the antibacterial ceramic described in this comparative example 1 is the same as that in Example 1, and the raw material composition of the antibacterial coating is also the same as that in Example 1. The only difference is that the raw materials of the green body are different. The green body described in the antibacterial ceramic of this comparative example 1 is composed of the following raw materials in parts by weight: 42 parts of pyrophyllite, 14 parts of cordierite, 18 parts of montmorillonite, 11 parts of wollastonite, 8 parts of magnesite, 7 parts of barite, 6 parts of cryolite, and 5 parts of lithium porcelain stone.
[0108] Comparative Example 2
[0109] The preparation method of the antibacterial ceramic described in this comparative example 2 is the same as that in Example 1, and the raw material composition of the green body is also the same as that in Example 1. The only difference is that the raw materials of the antibacterial coating are different. The antibacterial coating in the antibacterial ceramic of this comparative example 1 is composed of the following raw materials in parts by weight: 1.4 parts of polyvinylidene fluoride, 18 parts of N-methylpyrrolidone, and 1.5 parts of perfluorodecyltriethoxysilane.
[0110] According to JC / T897-2014 "Antibacterial Performance of Antibacterial Ceramic Products", the performance of the antibacterial ceramics prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the results are shown in Table 1 below:
[0111] Table 1 Performance test results of antibacterial ceramics
[0112]
[0113]
[0114] It can be seen from Table 1 that the antibacterial ceramics prepared in Examples 1-3 have excellent antibacterial properties. Comparison of Example 1 with Comparative Examples 1-2 shows that the green body and the antibacterial coating in the antibacterial ceramic cooperate with each other to ensure the long-lasting antibacterial properties of the prepared antibacterial ceramic.
Claims
1. An antibacterial ceramic, characterized in that: The invention is composed of a body and an antibacterial coating; the body is composed of the following raw materials in parts by weight: 40-43 parts of pyrophyllite, 12-15 parts of cordierite, 17-19 parts of montmorillonite, 10-12 parts of wollastonite, 7-9 parts of magnesite, 6-8 parts of barite, 5-7 parts of cryolite, 4-6 parts of lithium porcelain stone, 7-9 parts of silicon nitride, 11-13 parts of boron mud, 1-3 parts of nano lanthanum oxide, and 5-7 parts of nano zinc phosphate; the antibacterial coating is composed of the following raw materials in parts by weight: 2-3 parts of graphene oxide, 7-9 parts of modified red mud, 0.5-1.5 parts of 2-bromo-2-nitropropane-1,3-diol, 1.2-1.6 parts of polyvinylidene fluoride, 17-19 parts of N-methylpyrrolidone, and 1-2 parts of perfluorodecyltriethoxysilane; The preparation method of modified red mud consists of the following steps: ① After mixing red mud with water, hydrochloric acid was added to adjust the pH value of the system to 3, and then sodium hydroxide solution was added thereto to adjust the pH value of the system to 9, and finally filtered and washed with water until neutral, and dried at 125°C for 4h to prepare pretreated red mud; ② The pretreated red mud was mixed with copper nitrate solution, reacted at 80°C for 2.5 hours, and then filtered and dried to prepare modified red mud.
2. The antibacterial ceramic according to claim 1, characterized in that: The green body is composed of the following raw materials, by weight: 42 parts of pyrophyllite, 14 parts of cordierite, 18 parts of montmorillonite, 11 parts of wollastonite, 8 parts of magnesite, 7 parts of barite, 6 parts of cryolite, 5 parts of lithium porcelain stone, 8 parts of silicon nitride, 12 parts of boron mud, 2 parts of nano lanthanum oxide, and 6 parts of nano zinc phosphate.
3. The antibacterial ceramic according to claim 1, characterized in that: The antibacterial coating is composed of the following raw materials, measured in parts by weight: 2.5 parts of graphene oxide, 8 parts of modified red mud, 1.0 parts of 2-bromo-2-nitropropane-1,3-diol, 1.4 parts of polyvinylidene fluoride, 18 parts of N-methylpyrrolidone, and 1.5 parts of perfluorodecyltriethoxysilane.
4. The antibacterial ceramic according to claim 1, characterized in that: In step ①, the mass ratio of red mud to water is 1:1.5; The mass volume ratio of the pretreated red mud to the copper nitrate solution in step ② is 1:9, in g / mL; The concentration of the copper nitrate solution in step ② is 0.17 mol / L.
5. A method for preparing the antibacterial ceramic according to claim 1, characterized in that: It consists of the following steps: (1) The green body raw materials are uniformly mixed according to the weight ratio, wet ball-milled into slurry, dry-ground to obtain powder, and mold-pressed to obtain the green body; (2) drying the green body and then firing it, cooling it to room temperature at a cooling rate of 5-7°C / h to obtain an antibacterial ceramic green body; (3) dissolving graphene oxide and polyvinylidene fluoride in N-methylpyrrolidone to prepare a first solution; then dissolving modified red mud and 2-bromo-2-nitropropane-1,3-diol in perfluorodecyltriethoxysilane to prepare a second solution; adding the first solution to the second solution and stirring to prepare an antibacterial coating solution; (4) Spraying the antibacterial coating liquid onto the antibacterial ceramic body prepared in step (2), and then drying the body to obtain the antibacterial ceramic.
6. The method for preparing the antibacterial ceramic according to claim 5, characterized in that: The mass of water added during wet ball milling in step (1) accounts for 35% of the mass of the green body raw material and water, and the ball milling time is 18 hours; In step (1), the drying temperature is 100-105°C and the drying time is 7h; The pressure of the powder pressing in step (1) is 60 MPa.
7. The method for preparing the antibacterial ceramic according to claim 5, characterized in that: In step (2), the drying temperature is 105-110°C and the drying time is 4 hours; The sintering in step (2) is carried out by heating the temperature from room temperature to 750-800°C at a heating rate of 5°C / min and keeping the temperature for 55-65 minutes, and then heating the temperature to 1200-1225°C at a heating rate of 3°C / min and keeping the temperature for 2.5-3 hours.
8. The method for preparing the antibacterial ceramic according to claim 5, characterized in that: In step (3), the stirring temperature for preparing the first solution is room temperature, and the stirring time is 0.5 h; the stirring temperature for preparing the second solution is 130-135° C., and the stirring time is 0.8 h; the stirring temperature for the antibacterial coating liquid is room temperature, and the stirring time is 0.5 h.
9. The method for preparing the antibacterial ceramic according to claim 5, characterized in that: In step (4), the drying temperature is 80-85°C and the drying time is 4.5-5h.
Citation Information
Patent Citations
Antibacterial reinforced ceramic ware and preparation method thereof
CN107473721A
Antibacterial ceramic product and preparation method thereof
CN109437924A